Impacto do crescimento urbano nos serviços de saneamento básico no bairro Alto do Sumaré em Mossoró-RN - Silva, Gisley Carla Castro da (Universidade Federal Rural do Semi-Árido, 2020)
Sometimes, accelerated urban growth can negatively influence the dynamics that develop in cities. And in this scenario of growth and agglomeration of people, in increasingly smaller spaces, access to basic sanitation services directly reflects on the population's quality of life. In this context, through this research, the objective was to assess the impact of urban growth on the basic sanitation system in the Alto do Sumaré neighborhood, Mossoró-RN. The methodology consisted of the identification and characterization of the case study, data collection and processing (water consumption, housing, points of construction waste, urbanized blocks, streets), spatial modeling through the use of the Qgis program and analysis of the impact of urban growth. Through the results obtained, there was an increase in the urban density of the neighborhood, from 14.79% to 28.93% between the years 2009 to 2019 resulting in an increase of 101.15% in water consumption for the same reference period. In view of this evidence, the use of technological alternatives to manage water demand at the micro-measurement level has been proposed, such as the use of a dual-flush toilet bowl, a fact that would result in a 6.15% water saving. It was also found that the area of the urbanized block has decreased by 6.49% on average, as its number has grown (from 217 to 454), which may make the use of individual sewage systems in the area unfeasible. The density of civil construction waste points, of 11.27 points.km-2, shows the importance and urgency of elaborating an integrated civil construction waste management plan (PIGRCC), which contemplates public policies for the installation of voluntary waste delivery points. Finally, there was a need to encourage the implementation of alternatives aimed at increasing the non-permeable area in the urban region, which has been decreasing in view of the growing density of paved area in the neighborhood.
Keywords: Expansão urbana; Consumo de água; Esgotamento sanitário; Resíduos da construção civil; Drenagem; ENGENHARIAS::ENGENHARIA CIVIL